Conservation hotspots of insular endemic mammalian diversity at risk of extinction across a multidimensional approach - Leclerc, Camille; Magneville, Camille; Bellard, Céline (Diversity & distributions, 2022)
Aim Islands are one of the most threatened worldwide biotas. Based on their taxonomic diversity, some insular regions have been identified as key areas of conservation. Recently, systematic conservation planning has advocated for the use of multiple biodiversity facets to protect unique evolutionary and functional processes. Here, we identified priority areas for threatened insular endemic mammals across three key dimensions of biodiversity (taxonomic, phylogenetic, and functional), as well as their protection level and threats affecting them. Location Worldwide. Methods We applied diversity–area relationships to identify insular regions that harbored a disproportionately high rate of threatened endemic mammal diversity (whether taxonomic, phylogenetic, or functional) given their area for 1,799 islands across 19 insular regions. We also assessed the level of protection and the threats affecting biodiversity within each insular region. Results We showed a fairly good congruence between top‐ranked insular regions based on taxonomic, phylogenetic, and functional diversity. Specifically, we identified four hotspots for endemic mammalian conservation through the three diversity facets: Indo‐Burma, Madagascar and the Indian Ocean Islands, Mesoamerica and Galápagos Islands, and Wallacea. Except for Mesoamerica and Galápagos Islands, the protected areas coverage is low (<8%) within the hotspots. We also showed that most of the mammal species occurring in the hotspots was prone to either direct threats that affect their mortality or indirect threats that only alter their habitat, while mixed threats such as biological invasions or climate change were less represented in those regions. Main conclusions Our findings reinforce the importance of investigating the multiple diversity facets in a conservation concern and to link with the associated threats to ensure an effective conservation strategy.